Environmental effect on the leaf morphology and anatomy of Berberis microphylla G. Forst - Radice, Silvia (2015)
Berberis microphylla G. Forst is a fruit shrub native from Patagonia, considered as a non-timber forest product. In recent years, there has been an increased demand for its fruits, both for fresh and industrialized consumption, being the establishment of commercial orchards in different sites a need to meet this demand. B. microphylla cloned plants have been introduced from Ushuaia, Tierra del Fuego to Buenos Aires province in order to evaluate its phenotypic plasticity and the possibility of fruit production. At the same time, a comparative study on the morphology and anatomy of the mature leaves of B. microphylla grown in two different environmental conditions was carried out. Moreno leaves were significantly larger than Ushuaia leaves in all the morphological parameters registered, while Ushuaia leaves were more circular than Moreno leaves with the highest roundness and elongation indexes. Nevertheless, histological sections showed that Ushuaia leaves have one more layer of palisade cells respect to Moreno leaves. Ushuaia leaves showed higher palisade cells, larger abaxial epidermal cells and thicker cuticles than Moreno leaves. The stomatal density was superior on Moreno leaves. SEM of abaxial epidermis showed a surface with numerous ridges of different forms that prevent the layout of epidermal cells on Moreno leaves. Appearance of this surface is glossy and oily. On the contrary, epidermal cells are well recognized on Ushuaia leaves. Stomata of anomocytic type were observed and surface looks waxy. Auto-fluorescence on leaf cross sections were observed on the vascular bundles and partially on the epidermis cells. B. microphylla leaves showed a high phenotypic plasticity between the two sites of cultivation. The changes in the leaf morphology and structure observed in Moreno leaves could indicate that the plants are trying to adjust its morphology to the new culture conditions i.e. higher temperatures and lower irradiance.